Theoretical assessment on hetero-coordination of Alloys Silver-Antimony at Molten State - Panthi, Narayan; Bhandari, Indra Bahadur; Koirala, Ishwar (Himalayan Journal of Science and Technology, 2020)
The thermodynamic and structural properties of binary alloy Ag- Sb at temperature 1250K have been reported theoretically using quasi lattice model. The interchange energy has been considered a function of a temperature and thus various thermodynamic quantities are calculated at elevated temperature. The theoretical values of free energy of mixing, heat of mixing, entropy of mixing and chemical activity are reasonable agreement with experimental values in all concentrations of antimony from 0.1 to 0.9. The theoretical analysis tells that the alloy shows both ordering nature in Ag rich end and segregating nature in Sb rich end .The study reveals that the properties of alloy are asymmetric around equi-atomic composition. The Ag_3 Sn complexes are most likely to exist in the liquid state and are moderately interacting.